DIY or die? A typology of DIY careers in the Portuguese independent music scenes - Oliveira, A. (2023)
This article addresses the DIY career building strategies in the Portuguese independent music scenes. Is it anchored on the reading of DIY careers as a pattern of promoting employability, in a context marked by major transformations in the music industries and the precarization of professional trajectories. Drawing from interviews with 71 individuals involved in the production and mediation of Portuguese independent music, we seek to understand how these actors build their DIY careers considering their different positions within the music scenes, the strategies used to negotiate their careers, and the way DIY is present. For this, we conduct a typological reading of these careers to identify different career profiles. Based on a mixed-methods approach, we identify five distinct career profiles: ‘catch-all musicians’, ‘non-stop musicians’, ‘mediator musicians’, ‘author musicians’, and ‘mediators’. In their differences, these trajectories are marked by DIY ethos and praxis, from their beginnings to the present day.